Ultrahigh tensile transformation strains in new Ni50.5Ti36.2Hf13.3 shape memory alloy. (June 2016) - Wu, Y.; Patriarca, L.; Sehitoglu, H.; Chumlyakov, Y.
Abstract: We report on unprecedented transformation strains exceeding 20% in tension for Ni50.5 Ti36.2 Hf13.3 shape memory alloy (SMA). The strain measurements were made at multiscales utilizing advanced digital image correlation. The display of excellent strain reversibility in shape memory (isothermal deformation between Mf and Af ), isobaric thermal cycling (between Mf and Af ), and superelasticity experiments (deformation above Af ) confirms a wide range of functionality. The ultrahigh strains in [111] orientation exceed the lattice deformation theory predictions possibly pointing to contributions from mechanical twinning effects. The high strength levels and large strains result in very high work outputs compared to other SMAs. Graphical abstract: